Problem bohatera w opowiadaniu A.P. Czechowa „Czarny mnich” - Chudzińska-Parkosadze, Anna (Studia Rossica Posnaniensia, 2011)
This article is focused on the ontological issues that are reflected in one of the most philosophical stories written by A.P. Chekhov – The Black Monk. The core idea on which the construction of the hero and the presented world are based turns out to be dualism. Kovrin belongs to the upper world of idea, so consequently, this status brings him to the conflict with the usual people – the dwellers of the world of the matter. This platonic philosophy seems to reflect not only a certain artistic strategy of the writer, but also a personal view on the human existence in the world of Chekhov himself. What needs to be underlined is the fact, that the writer seems to believe that in the process of human evolution the number of people belonging to the realm of idea will increase in the future.